Japanese Slang on The Nihongo Mantappu Youtube Channel (Morphosemantic Study) - Dewi, Nastasya Kirana; Novitasari, Raden (IZUMI, 2022)
Language is a means of communication and interaction among humans to share information from all over the world, therefore language has a very important role in human life. Slang is a variety of non-formal language used by people aged 10-30 years. Slang can also be used as a secret form by using words that can be understood by certain circles and are temporary. By using this slang, it means that we are people who follow the times. Slang can also be modified and can create new vocabulary. The purpose of this study is to examine and describe the form, meaning, and process of forming Japanese slang words found on the Nihongo Mantappu Jerome Polin youtube channel. The method of data collection used the method of observing with note taking techniques, and the method used in the analysis was a qualitative descriptive method. The research data is in the form of slang that appears on the Nihongo Mantappu Jerome Polin Youtube channel. The data collected were 19 Japanese slang data with various variations of forms and meanings. The theory used to analyze is the theory proposed by Kageyama (2016) regarding the process of word formation. The results obtained according to Kageyama's theory (2016) are the process of forming Japanese slang words consisting of compounding (C), affixation (A), conversion (K), reduplication (R), blending (B), clipping (C), and acronyms. or initials (I). gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor